2014
DOI: 10.1002/2013jd021120
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric gravity waves due to the Tohoku‐Oki tsunami observed in the thermosphere by GOCE

Abstract: Oceanic tsunami waves couple with atmospheric gravity waves, as previously observed through ionospheric and airglow perturbations. Aerodynamic velocities and density variations are computed from Gravity Field and Steady-State Ocean Circulation Explorer (GOCE) accelerometer and thruster data during Tohoku-Oki tsunami propagation. High-frequency perturbations of these parameters are observed during three expected crossings of the tsunami-generated gravity waves by the GOCE satellite. From theoretical relations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…As discussed above, Cf3 is a marker of GW perturbations measured along the GOCE orbit. The advantage of this new parameter compared to the C 3 index computed in the time domain by Garcia et al [] is that it allows to characterize the frequency content of GW perturbations observed in the GOCE data. In addition, we can use equation to relate the dominant frequency observed in GOCE data to the maximum horizontal wavelength of GWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed above, Cf3 is a marker of GW perturbations measured along the GOCE orbit. The advantage of this new parameter compared to the C 3 index computed in the time domain by Garcia et al [] is that it allows to characterize the frequency content of GW perturbations observed in the GOCE data. In addition, we can use equation to relate the dominant frequency observed in GOCE data to the maximum horizontal wavelength of GWs.…”
Section: Resultsmentioning
confidence: 99%
“…Because of GW polarization, the cross‐track wind component VGWc can be written [ Garcia et al , ]: VGWc=β(ω)ΓGW with β ( ω ) being nonzero only in the frequency (e.g., horizontal wavelength) range corresponding to GWs. Our analysis filters out the long‐term variations ρ 0 and V0c and uses the time derivative of relative air density fluctuations ( trueΓ̇).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several developments have motivated a renewed interest in AGW theory. Ground-breaking observational techniques (Nishida, Kobayashi & Fukao 2013;Garcia et al 2014) have provided new insights into atmospheric waves. AGWs couple wave processes in the solid earth and the ocean with those in the ionosphere and thermosphere (Watada 2009;Godin & Fuks 2012;Ardhuin & Herbers 2013;Godin, Zabotin & Bullett 2015) and, thus, underlie radar observations of earthquakes (Maruyama et al 2012;Astafyeva et al 2013) and satellite detection of tsunamis (Makela et al 2011;Occhipinti et al 2013;Garcia et al 2014;Coïsson et al 2015).…”
mentioning
confidence: 99%
“…Ground-breaking observational techniques (Nishida, Kobayashi & Fukao 2013;Garcia et al 2014) have provided new insights into atmospheric waves. AGWs couple wave processes in the solid earth and the ocean with those in the ionosphere and thermosphere (Watada 2009;Godin & Fuks 2012;Ardhuin & Herbers 2013;Godin, Zabotin & Bullett 2015) and, thus, underlie radar observations of earthquakes (Maruyama et al 2012;Astafyeva et al 2013) and satellite detection of tsunamis (Makela et al 2011;Occhipinti et al 2013;Garcia et al 2014;Coïsson et al 2015). Vertical transport of horizontal momentum by atmospheric waves plays a crucial role in large-scale circulation of the middle and upper atmosphere, and the development of climate models requires vastly improved parameterizations of the momentum flux (Vadas & Liu 2009;Geller et al 2013;Jia et al 2014 andSchirber et al 2014).…”
mentioning
confidence: 99%